2023
DOI: 10.1021/acs.chemrestox.3c00128
|View full text |Cite
|
Sign up to set email alerts
|

Enantiomeric Fractions Reveal Differences in the Atropselective Disposition of 2,2′,3,5′,6-Pentachlorobiphenyl (PCB 95) in Wildtype, Cyp2abfgs-Null, and CYP2A6-Humanized Mice

Abstract: Polychlorinated biphenyls (PCBs) are environmental contaminants that can cause neurotoxicity. PCBs, such as PCB 95 (2,2′,3,5′,6-pentachlorobiphenyl), can be metabolized by cytochrome P450 enzymes into neurotoxic metabolites. To better understand how the metabolism of PCB 95 affects neurotoxic outcomes, we conducted a study on the disposition of PCB 95 in transgenic mouse models. The mice were given a single oral dose of PCB 95 (1.0 mg/kg) and were euthanized 24 h later for analysis. PCB 95 levels were highest … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 73 publications
0
1
0
Order By: Relevance
“…Studies with PCB136, a PCB congener structurally related to PCB52, showed that this congener is oxidized in a sex-dependent manner by precision-cut rat liver tissue slices. Oral dosing studies in rodent models reported conflicting results, with most studies not observing sex differences in the disposition of PCBs and their metabolites. ,,, Thus, the sex-dependent metabolite formation following PCB52 inhalation has implications for PCB52 neurotoxicity because OH-PCBs can affect cellular targets relevant to PCB neurotoxicity . Further studies are needed to identify the absorption, distribution, metabolism, and elimination processes that contribute to sex differences in the toxicokinetics of PCB52 metabolites following the inhalation of PCB52.…”
Section: Resultsmentioning
confidence: 99%
“…Studies with PCB136, a PCB congener structurally related to PCB52, showed that this congener is oxidized in a sex-dependent manner by precision-cut rat liver tissue slices. Oral dosing studies in rodent models reported conflicting results, with most studies not observing sex differences in the disposition of PCBs and their metabolites. ,,, Thus, the sex-dependent metabolite formation following PCB52 inhalation has implications for PCB52 neurotoxicity because OH-PCBs can affect cellular targets relevant to PCB neurotoxicity . Further studies are needed to identify the absorption, distribution, metabolism, and elimination processes that contribute to sex differences in the toxicokinetics of PCB52 metabolites following the inhalation of PCB52.…”
Section: Resultsmentioning
confidence: 99%